Human Papilloma Virus Vaccine: Future of Cervical Cancer Prevention (Journal of Enam Medical College, 2016)
Cervical cancer is a deadly cancer that clutches lives of the women in most of the cases due to lack of consciousness about the disease in the developing countries. It remains a threat which is second only to breast cancer in overall disease burden for women throughout the world. Cervical cancer is almost a preventable disease by prophylactic vaccine and routine screening. Both Cervarix and Gardasil vaccines have been effective in preventing persistent infection with targeted HPV types and in preventing cervical intraepithelial lesions. It is safe and nearly 100% effective if given before onset of sexual activity. This review article is aimed to explore different aspects of this vaccine as well as to develop awareness among health professionals of different disciplines.J Enam Med Col 2016; 6(3): 157-160